Wird Schon Stimmen! A Degree Operator Analysis of Schon. (11th September 2018) - Zimmermann, Malte
Abstract: The article puts forward a novel analysis of the German modal particle schon as a modal degree operator over propositional content. The proposed analysis offers a uniform perspective on the semantics of modal schon and its aspectual counterpart meaning 'already': Both particles are analyzed as denoting a degree operator, expressing a scale-based comparison over relevant alternatives. The alternatives are determined by focus in the case of aspectual schon (Krifka 2000 ), but are restricted to the polar alternatives p and $\neg p$ in the case of modal schon . Semantically, modal schon introduces a presupposition to the effect that the circumstantial conversational background contains more factual evidence in favor of p than in favor of $\neg p$, thereby making modal schon the not at-issue counterpart of the overt comparative form eher 'rather' (Herburger & Rubinstein 2014 ). The analysis incorporates basic insights from earlier analyses of modal schon in a novel way, and it also offers new insights as to the underlying workings of modality in natural language as involving propositions rather than possible worlds (Kratzer 1977, 2012) .